Facework and (im)politeness in professional communication: an analysis of debt collection encounters - Harrington, Leigh (2023)
This thesis makes major contributions to the theorisiation of face, the central concept in (im)politeness research. Existing conceptions of face are evaluated and new advancements are proposed, using empirical evidence of facework in debt collection encounters, a uniquely complex and under-researched professional context in pragmatics research. A dataset of 110 authentic telephone-mediated debt collection encounters between a debt collector and debtors were recorded at a UK-based credit union. The methodological approach to analysing this interactive data combines ethnographic knowledge of the credit union and my own experience of working in a similar debt collection context. The analysis is supplemented with interviews from credit union staff. The findings demonstrate that current conceptions of face cannot account for every aspect of facework exhibited in this data. Hence, four innovative advancements in the theorisation of face are proposed which enable (im)politeness analysts to more comprehensively explore, capture, and understand the complex ways that face manifests and is managed in professional contexts. These new and sophisticated analytical tools include two expansions to the concept of face. Multi-situational face is the first notion of face in (im)politeness research to specifically foreground face’s potentially diffuse temporal qualities in the form of retrospective and projected face-wants. The concept of constructed institutional face develops understanding of the types of face professionals must manage in local discourse by theorising that interlocutors in professional-lay encounters can orient to or perform face for an organisation. Additionally, the original category of synthetic facework represents the first coherent classification of facework strategies that attempt to have an instrumental effect on an interlocutor via superficial means. Lastly, the potentially metonymic relationship between positive face and evaluative entities that are rooted in the real world is emphasised. The thesis is the first in (im)politeness research to offer a linguistically-informed framework for practically implementing its recommendations regarding the linguistic volition of professionals into real-world workplace settings. As the principal empirical investigation of actual debt collection discourse practices, the thesis contributes to multidisciplinary scholarship on debt, which is an important social, cultural, and economic issue in contemporary British society.